Innovation and Biotechnology Utilizing Local Microorganisms to Improve the Nutrient Quality of Fermented Cassava Peel Feed: Roni's Article - Yulianto, Roni; Asfal Hidayatullah, Nabil; Nur Widodo (International Integrated Agricultural Journal (IIAJ), 2026)
An alternative feed supply can be achieved by utilizing cassava peel agricultural waste as ruminant feed. Fermentation is a feed processing technique using microorganisms to improve feed quality. This study aimed to determine the effect of using different local microorganisms to improve the nutrient quality of fermented cassava peel waste as livestock feed. The materials of this study used cassava peel, rice bran, rice washing water, effective microorganisms, brown bottles, banana stems, young bamboo, fruit waste, and molasses. The fermentation process used the Solid-State Fermentation (SSF) for 12 days with 4 treatments and 4 replications. P0: control (EM-4); P1: Banana Stem MOL; P2: Young Bamboo MOL; P3: Crystal Guava and Pineapple Waste MOL. The fermented feed was analyzed using proximate analysis in the laboratory. The research design used a Completely Randomized Design (CRD). The research data were tested statistically by ANOVA and continued with Dunnett's further test to determine the significantly different interactions (P<0.05) between treatments. The result study was cassava peel fermentation showed the best results in crude protein content in P1 (8.65%) and P3 (8.51%), and ash content in P0 (0.52%), while organic matter, dry matter, and crude fiber showed unsignificant results (P>0.05). Local microorganisms from banana stems, bamboo shoots, and fruit waste can be used as a substitute for commercial biostarter EM-4 for fermented feed fermenters). It can be carried out on the application of fermented feed on digestibility and productivity of ruminant livestock.